Pengaruh Kualitas Pelayanan Terhadap Loyalitas serta Kepuasan Masyarakat sebagai Variabel Intervening pada Kantor Sekretariat Baitul Mal Kabupaten Aceh Barat - Arkadius, Ahmad; Safriani, Ida (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to determine the Quality of Service Affects Loyalty with Community Satisfaction as an Intervening Variable at the Secretariat Office of Baitul Mal, West Aceh Regency. The population in this study were all people who visited the Secretariat Office of Baitul Mal, West Aceh Regency. While the sample in this study was 100 people and the sampling technique was carried out randomly (Random Sampling). Based on the results of testing carried out using path analysis, namely the service quality variable, there is a significant influence on customer satisfaction with a coefficient value of 0.604. Furthermore, by using the t-test calculation in the regression test and path analysis where service quality and customer satisfaction simultaneously affect customer loyalty. Furthermore, testing the service quality variable has a significant effect on customer loyalty with a coefficient value of 0.217. Then the results of this study also prove that customer satisfaction also has a significant effect on customer loyalty of 0.539. Service quality has a direct influence on customer loyalty of 21.7% and an indirect influence of 32.5%, due to the presence of a mediating variable, namely customer satisfaction. So the total influence is 54.2%.